2012
DOI: 10.1002/jbm.a.34280
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of pro‐osteogenic responses by a bioactive ceramic coating

Abstract: The objective of this study was to analyze the responses of bone-forming osteoblasts to Ti-6Al-4V implant material coated with silica-calcium phosphate nanocomposite (SCPC50). Osteoblast differentiation at the interface with SCPC50-coated Ti-6Al-4V was correlated to the adsorption of high amount of serum proteins, high surface affinity to fibronectin, Ca uptake from and P and Si release into the medium. SCPC50-coated Ti-6Al-4V adsorbed significantly more serum protein (p < 0.05) than control uncoated substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 69 publications
0
26
0
Order By: Relevance
“…However, bioceramic dissolution in presence and absence of cells is not analogous, in fact, the dissolution-precipitation reactions and ECM mineralization are strongly cell-mediated. 12,13 The adsorption of proteins and biological macromolecules is considered to be the first stage during implant integration, followed by cell attachment. 14 Protein adsorption on biomaterials, however, is not an "across-the-board" phenomenon; the surface chemistry of the material controls the species and conformation of proteins that it adsorbs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bioceramic dissolution in presence and absence of cells is not analogous, in fact, the dissolution-precipitation reactions and ECM mineralization are strongly cell-mediated. 12,13 The adsorption of proteins and biological macromolecules is considered to be the first stage during implant integration, followed by cell attachment. 14 Protein adsorption on biomaterials, however, is not an "across-the-board" phenomenon; the surface chemistry of the material controls the species and conformation of proteins that it adsorbs.…”
Section: Introductionmentioning
confidence: 99%
“…21 In vitro studies have shown that SCPC50 coating stimulated biological hydroxyapatite formation, enhanced osteoblast differentiation, and induced a low level immunogenic response as compared to the cells attached to uncoated Ti-6Al-4V substrates. 13,21,22 The objective of the present study is to investigate the synergistic effects of surface roughness and material chemistry of SCPC50 coating on modulating key early cellular functions leading to osteoblast differentiation on orthopedic implants. Temporal variations in cell morphology and cytoskeletal organization have been analyzed and correlated to the topography and ionic dissolution of the bioactive ceramic.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the absorption of high Ca concentration, the attached stem cells produced calcified nodules and mineralized extracellular matrix (27,28) . On the mRNA level, qRT-PCR revealed that osteopontin and osteocalcin mRNA expression by osteoblast-like cells attached to SCPC50 was significantly higher than that on SCPC10, HA-200 or polystyrene after 2 days in culture (30)(31)(32)(33) .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…Silica, in turn, plays an important role in bone marrow cell differentiation, increasing the phenotypic expression of osteoblasts . In addition, it has been demonstrated that this type of implant coating induces higher protein adsorption, enhancing bone integration while minimizing the induction of inflammatory responses …”
Section: Introductionmentioning
confidence: 99%
“…19 In addition, it has been demonstrated that this type of implant coating induces higher protein adsorption, enhancing bone integration while minimizing the induction of inflammatory responses. 20 The aforementioned issues prompted the present work, in which a novel use of WJ as a three-dimensional matrix in combination with BC (HA and btricalcium phosphate, b-TCP) and BG particles, is proposed. This kind of combination would generate a synergistic effect resulting in a bone-like tissue, enhancing the biological and mechanical behavior of BCO.…”
Section: Introductionmentioning
confidence: 99%